Design of Two Phase DC-AC Interleaved Boost Inverter with Voltage Control System using PI Controller - Juan Marco Alexander Wasiatno; Leonardus Heru Pratomo (Jurnal Elektronika dan Telekomunikasi, 2024)
DC-DC Interleaved Boost Converter (DC-DC IBC) topology was developed through the interleaving technique since conventional DC-DC Boost Converter has many problems related to complex circuit control, harmonics, and output power. In this research, DC-DC IBC was developed into a Two-Phase AC-AC Interleaved Boost Converter (TP AC-AC IBC), then combined with a Two-Phase Full Bridge Inverter to become a Two-Phase DC-AC Interleaved Boost Inverter (TP DC-AC IBI). TP DC-AC IBI has several advantages, including minimal current and voltage ripples and greater output power because it consists of two AC-AC IBCs. This research aims to meet highly regulated AC voltage needs with the renewable energy source input using the proposed topology, by implementing Proportional Integral (PI) close loop control system. The output voltage is detected using a voltage transducer LV-25P, then compared with a reference voltage and controlled using a PI controller to keep the output voltage consistently stable. The switching signal setting uses the Sinusoidal Pulse Width Modulation (SPWM) technique by modulating the control output with a high frequency. As a verification step, testing was carried out using Power Simulator (PSIM) software and then validated by hardware testing in the laboratory. Testing was carried out using several test signals, and it was found that the proposed method worked well. System efficiency and Total Harmonic Distortion (THD) tests carried out using various load values, and a maximum efficiency of 93.87% and a minimum THD of 2.46% were obtained.